2015
DOI: 10.1038/npjcompumats.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

The Open Quantum Materials Database (OQMD): assessing the accuracy of DFT formation energies

Abstract: The Open Quantum Materials Database (OQMD) is a high-throughput database currently consisting of nearly 300,000 density functional theory (DFT) total energy calculations of compounds from the Inorganic Crystal Structure Database (ICSD) and decorations of commonly occurring crystal structures. To maximise the impact of these data, the entire database is being made available, without restrictions, at www.oqmd.org/download. In this paper, we outline the structure and contents of the database, and then use it to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
1,277
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,663 publications
(1,331 citation statements)
references
References 69 publications
46
1,277
2
6
Order By: Relevance
“…It turns out that the difference between good glass formers and bad ones depends on the number and energies of unstable crystal structures that 'compete' with the ground state while the alloy cools down 10 . Wolverton's OQMD includes around 400,000 hypothetical materials, calculated by taking a list of crystal structures commonly observed in nature and 'decorating' them with elements chosen from almost every part of the periodic table 9 . It has a particularly wide coverage of perovskites -crystals that often display attractive properties such as superconductivity and that are being developed for use in solar cells as microelectronics.…”
Section: Materials Genomicsmentioning
confidence: 99%
“…It turns out that the difference between good glass formers and bad ones depends on the number and energies of unstable crystal structures that 'compete' with the ground state while the alloy cools down 10 . Wolverton's OQMD includes around 400,000 hypothetical materials, calculated by taking a list of crystal structures commonly observed in nature and 'decorating' them with elements chosen from almost every part of the periodic table 9 . It has a particularly wide coverage of perovskites -crystals that often display attractive properties such as superconductivity and that are being developed for use in solar cells as microelectronics.…”
Section: Materials Genomicsmentioning
confidence: 99%
“…This is not only true for the quantities discussed in this work. Recently, Kirklin et al [66] concluded that the mean absolute error on experimental formation energies was of comparable size (0.082 eV/atom) to the average absolute difference between DFT and experiment (0.096 eV/atom).…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, databases of materials have been created containing structural information of both experimental and theoretical compounds from highthroughput calculations, which are the basis for data-mining techniques in materials discovery projects. [1][2][3][4][5][6][7] On the other hand, ab initio structure predictions [8][9][10][11][12][13][14][15] can produce a huge number of new structures that have either not yet been found experimentally or are metastable. [16][17][18][19][20][21] In both cases, it is essential to quantify similarities and dissimilarities between structures in the data sets, requiring a configurational distance that satisfies the properties of a metric.…”
Section: Introductionmentioning
confidence: 99%